Construction Supply Chain Risk Analysis in Bima - junna, isra; asfarina, sharwanda; Fikar, M Ziaul; Winardin, Sofyan; Apriansyah, Muh (Jurnal Media Informatika, 2024)
The construction business is a complex business, in terms of time management and budget management. A common problem is construction supply chain management. Risks often occur due to changes in construction models and the wrong choice of supply chain, such as the mobilization of materials from the factory to the project site is often late because it is not well organized. Construction supply chain management is an idea that regulates the supply chain construction cycle by identifying risks that can cause project failure. Risks identified at the construction stage can reduce risks in construction projects. The identified risks are then analyzed using a simulation model so that the right strategy can be given to estimate project delays, especially in terms of time and cost. The purpose of this study is to provide strategic solutions to risky supply chain activities in construction projects. Monte Carlo simulations are carried out using the Microsoft Excel application. Based on the final results of the study, of the thirty risks targeted by the Monte Carlo simulation, four risks are included in the high risk analysis, eleven risks are included in the medium risk analysis, and fifteen risks are included in the low risk analysis. The four risks that are included in the high score are then discussed by the contractor's project manager, especially to understand the risk management strategy. The response to these four risks is to reduce the risk by following the operational standards of construction projects, which include material inspection and work execution, as well as ensuring that the amount of material in the warehouse is not less than 30% so that there is no waiting time in the field.